Hubungan Kandungan Minyak Dengan Kelimpahan Diatom Pada Strata Kedalaman Di Perairan Tanjung Buton Kabupaten Siak - Nurul Abdiah Nasution; Yusni Ikhwan Siregar; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
A study on the oil content of sea water and diatom abundance wereconducted in March 2016 at Tanjung Buton consist of three sampling station wereestablished with three depth strate (upper, midlle and lower) on each station. Theidentification and quantification of oil content as well as diatom were carried outin Marine Chemistry Laboratory, Faculty of Fisheries and Marine Science,University of Riau in Pekanbaru. The result of the study showed that oilcontents range apparently the highest of oil content were found at station 1(0,1603 ppm) and the lowest was found at station 2 (0,0994 ppm). The highestdiatom abundance was found at stasion 3 (352 cells/L) and the lowest abundancewas found at station 1 (289 cell/l). 18 species of diatom were found in TanjungButon Water. Nitzchia sp was the species with the highest dominance. Oil contentwith diatom abundance showed a weak negative corelation Y= 266,2-3,915x; R² =0,118; r = 0,344. At the upper showed a very weak negative corelation Y = 318,7-0,070x; R² = 2 X 10-9 ; r = 0,00014, at the midlle showed a weak positivecorelation Y = 236,2+615,2x; R² = 0,141 ; r = 0,3755 while at lower showed avery weak negative corelation Y = 492-1477x ; R² = 0,149 ; r = 0,386 whichmean increasing oil content will cause a decrease the abundance of diatom inTanjung Buton water’s.Key word’s : Oil content, diatom, Tanjung Buton Water